The Influence of Allport and Cattell's Big Five Personalities on Learning Styles - Mumu Munawar; Eva Syarifatul Ma’rifati Siti Maldani; Tarsono (al-Afkar, Journal For Islamic Studies, 2025)
A person's personality plays a significant role in determining how they learn and interact with the educational environment. One widely used personality theory is the Big Five Personality, which consists of five main dimensions: openness to experience, conscientiousness, extroversion, agreeableness, and neuroticism. This study aims to analyze the influence of Allport and Cattell's Big Five Personality dimensions on students' learning styles at SMK Igasar Pindad. These personality dimensions are believed to influence how students absorb information and adapt to existing learning methods. The method used in this study is a quantitative approach with a survey design. Data were collected through a questionnaire that measures the Big Five personality dimensions and students' learning styles. The sample of this study consisted of 100 SMK Igasar Pindad students. Data analysis was conducted using SPSS software for Pearson correlation and linear regression tests to examine the relationship between personality dimensions and students' learning styles. The results showed that the dimensions of openness to experience and extroversion had a significant positive relationship with kinesthetic and visual learning styles, while the dimension of conscientiousness was positively correlated with a more structured and detailed learning style. On the other hand, the dimension of neuroticism showed a negative influence on learning styles involving high pressure, such as auditory learning styles that require high concentration in challenging situations. These findings provide important insights for educators to understand how students' personalities influence their learning style preferences, so they can design more effective and adaptive learning strategies according to student characteristics.